Pengaruh Content Digital marketing dan Penggunaan Platfrom Instagram Terhadap Keputusan Pembelian pada JimsHoney Kota Malang (Studi pada Mahasiswa FEB Unisma Angkatan 2021) - Wahyuningtyas, Novianur; Hidayati, Nur; Saraswati, Ety (UNIVERSITAS ISLAM MALANG, 2025)
Abstract This study aims to understand the influence of Content Digital marketing and the Use of the Instagram Platform on Purchase Decisions of Jimshoney in Malang City. The sampling technique applied is purposive sampling, with a total sample of 90 respondents. Data collection was carried out through questionnaire distribution. The data analysis technique used in this study is multiple linear regression. The results indicate that, Content Digital marketing and the Use of the Instagram Platform have a positive and significant impact on Jimshoney's Purchase Decisions. Keywords: Content Digital Marketing, Use of Instagram Platfrom, Purchase Decisions, Jimshoney, Social Media